Prevalence and Antibiogram of Escherichia coli and Staphylococcus spp. Isolated from Cattle Milk Products Sold in Juja Sub-County, Kenya - Julius I. N. Sombie; John Kagira; Naomi Maina (Journal of Tropical Medicine)
Dairy ruminant milk provides a conducive environment for bacterial proliferation. In animals, these bacteria are exposed to antibiotics, whose overuse has led to increased cases of drug resistance. A cross-sectional study was conducted on milk and milk products vended in Juja Sub-County, Kenya to determine the prevalence of bacteria and antibiogram of Staphylococcus spp. and Escherichia coli. A total of 169 milk samples were obtained from various outlets in the study area. Milk samples were cultured and isolated bacteria were identified using standard bacteriological procedures. Various bacteria (15 species) were isolated in different proportions. Staphylococcus spp. and E. coli were isolated from 25.4% and 11.8% of the collected samples, respectively. The highest number of Staphylococcus spp. were isolated from raw milk (n = 34) while the highest number of E. coli where isolated from fermented milk (n = 15). Staphylococcus spp. and E. coli isolates were subjected to antimicrobial susceptibility tests using CLSI guidelines. The Staphylococcus spp. isolates were highly resistant to penicillin G (93%) but susceptible to norfloxacin (100%), gentamicin (90.6%), and chloramphenicol (86%). The E. coli isolates were highly resistant to cephalexin (85%) and ceftazidime (60%) but susceptible to chloramphenicol (100%), norfloxacin (95%), gentamicin (95%), azithromycin (95%) and cefepime (80%). Furthermore, 44.3% of Staphylococcus spp. and 50% of E. coli isolates had a Multiple Antibiotic Resistance (MAR) Index greater than 0.2. This implies that these bacteria were high-risk bacteria whose treatment with current antibiotics would be challenging. The high prevalence and multidrug resistance patterns shown by the Staphylococcus spp. and E. coli isolated from milk products in Juja Sub-county highlights the importance of proper handling and processing of milk from the farm to consumers. This will in turn reduce the possibility of zoonotic transfer of multidrug-resistant bacteria.